Reverse engineering of formaldehyde in cosmetic products using rp-hplc technique by derivatization with 2, 4-dinitrophenylhydrazine - SUSHAMA R. AMBADEKAR; DEEPAK BABURAO NIKAM; CHANDAN B. WARKAR (International Journal of Pharma and Bio Sciences, 2019)
Formaldehyde is a known carcinogen which is hazardous for health. Formaldehyde is used in cosmetic products to prevent microbial growth. Being a carcinogen, it is very much essential to monitor trace level formaldehyde in cosmetic products available in market. Hence, a simple, precise, accurate, and sensitive RP-HPLC method for determination of formaldehyde in cosmetic products was developed. The chromatographic separation of formaldehyde was achieved with C18, 250 x 4.6 mm, 5 µm column. The mobile phase Water: Acetonitrile (57:43) was delivered at a flow rate of 1.5 mL/min. Formaldehyde is not easily ionisable and cannot be easily analysed by Mass Spectrometry as well as Gas Chromatography. Formaldehyde lacks intrinsic chromophore or flurophore and is volatile in nature which restricts direct detection of formaldehyde in complex matrices. To overcome these limitations, the sample was dissolved in selected solvent and derivatized with 2,4-dinitrophenylhydrazine to form 2,4-dinitrophenylhydrazone with UV absorbance maxima at 365 nm. Hence, detection was performed at 365 nm. Chromatographic run completed within 20 min. Developed method was subjected for validation to check suitability for quantification of formaldehyde in cosmetic samples. Validation is performed in accordance with International Conference on Harmonization (ICH) Q2 (R1) guideline. The calibration curve was found to be linear with correlation coefficient close to 1.0 over a concentration range of 0.4 to 4.0 ppm of formaldehyde. The RSD for intra-day and inter day precision was <5.0%. Limit of detection (LOD) of the method was found as low as 0.2 ppm and Limit of quantification (LOQ) of the method was found 0.4 ppm. Validation results proved that developed method is highly sensitivity, specific, linear, accurate, reproducible and robust for quantification of trace level (ppm) formaldehyde. Selected cosmetic samples were analysed with validated method. Observed results were reproducible. This method can be applied to determine formaldehyde content in other cosmetic samples such as creams, shampoos and other skin care products.